Eksperimen Pembelajaran Matematika Dengan Strategi Brain Based Learning dan Problem Based Learning Terhadap Hasil Belajar Ditinjau Dari Kemampuan Berpikir Kritis Siswa Kelas Vii Mts Negeri Ketanggung Tahun Ajaran 2015/2016 - HAYYI' MUTHOHHAROH, NUR (2016)
The purpose of research this are: (1) To examine the influence of Brain Based Learning and Problem Based Learning strategy toward student learning outcomes. (2) To examine the influence of critical thinking skills toward student learning outcomes. (3) To examine the interaction between learning strategy and critical thinking skills toward student learning outcomes. The type of the research is quantitative research with quasi experimental design. The population of the research is all of student seventh grade at MTs Negeri Ketanggung, the sample of research is VIIA and VIIB graders. The technique of collecting data with methods of testing and documentation. The technique of analyzing data by using the unbalanced two-way analysis of variance. The finding of the research with α = 5%: (1) There is influence of learning strategy Brain Based Learning and Problem Based Learning toward student learning outcomes, (2) There is influence of critical thinking skills toward student learning outcomes, (3) There is no efect interaction between learning strategy and critical thinking skills toward student learning outcomes.